Clinical quantitative evaluation of tooth wear: a 4-year longitudinal study - Korkut, Bora; Tagtekin, Dilak; Murat, Naci; Yanikoglu, Funda (Quintessence Publishing, 2020)
Purpose: This study investigated the progression of incisal tooth wear clinically for 4-years, using various diagnostic methods. Effectiveness of occlusal splints (night guards) for patients with nocturnal bruxism was also evaluated. Materials and Methods: Forty maxillary incisors from 10 patients with nocturnal bruxism were selected. Group 1 (n=5) wore occlusal splints for 6 months, whereas group 2 (n=5) didn't. Ultrasound, cast-model analysis (control), digital radiography, FluoreCam and colorimeter were used for measurements. Clinical progression of incisal wear monitored at baseline, 3, 6, 12, 24 and 48 months, respectively. Results: Ultrasound, cast-model analysis and FluoreCam readings gradually and statistically significantly decreased during the overall evaluation period for both groups (p<0.001). Regarding colorimeter, statistically significant differences in periodical measurements were observed from 24 months and 12 months, for group 1 and group 2, respectively (p<0.001). There were no statistically significant differences in readings at evaluation periods, between the groups, for ultrasound, digital radiography and cast-model analysis (p >= 0.05): however, statistically significant differences were observed for colorimeter at 24 months (p=0.010) and 48 months (p<0.001), and for FluoreCam at 12, 24. 48 months (p<0.001). Annual decrease in mean crown length was determined as 20-30 pm for group 1 and 40-50 pm for group 2. The decreases in mean crown length were statistically significantly lower for group 1 compared to group 2, regarding the assessments for 1 year, 2 years and 4 years (p<0.001). Positive and good correlations were observed between ultrasound, cast-model analysis and FluoreCam measurements (p<0.001). Conclusions: Ultrasound. FluoreCam and colorimeter showed promising results for monitoring any change and progression of incisal tooth wear clinically. Ultrasound might be considered as a quantitative, reliable and repeatable method. Precision of the measurements varied among the diagnostic methods used. Occlusal splints may have a potential preventive effect for progressive tooth wear.
Keywords: Bruxism; Colorimeter; Fluorescence; Occlusal Splints; Tooth Wear; Ultrasound